A framework for devicecentric sensing cloud. (2015) - Distefano, Salvatore; Merlino, Giovanni; Puliafito, Antonio
Sensing and actuation as a service (SAaaS) is a paradigm, modelled after cloud computing and serviceoriented architectures, which features a 'devicecentric' IaaSlike provisioning model for actual, even if virtual, sensors and actuators, against the 'datacentric' one mainly just gathering and manipulating sensed data. In the past, we outlined a reference architecture meant to address the requirements SAaaS brings about, such as the involvement of both mobiles and sensor networks. This was a first step towards a static view of the solution, still to be expanded to develop a clearer picture about the application of the approach to specific use cases. This paper thus addresses the topic by providing a modular architecture described from both static and dynamic perspective of a SAaaS framework implementing the basic facilities required for building up a sensing cloud. We thus identified, designed and implemented a mobile crowdsensing app to explore an interesting use case, described to showcase a practical and useful scenario where an SAaaS cloud may be successfully employed.